Przechwycenie niemieckiej wyprawy bombowej przez polskie myśliwce w okolicach Aleksandrowa Kujawskiego w dniu 4 września 1939 r. znane w literaturze jako bitwa nad Poczałkowem, w świetle źródeł (Tabularium Historiae, 2019)
In the defensive war of 1939, despite the crushing quantitative and technical disproportion in favor of Germany, the Polish air force fought many air clashes and battles with Luftwaffe planes. Among them were both defeats and victorious duels in favor of the Poles. One of the most spectacular was the Battle of Poczałkowo, a village near Aleksandrów Kujawski. The battle took place in the early afternoon of September 4. On that day, PZL P-11c fighter planes belonging to the Toruń III/4 Fighter  Squadron, commanded by Flight Lieutenant Tadeusz Rolski, attacked dozens of German Junkers Ju 87 machines returning from bombing military and civilian targets, flying in the cover of Messerschmitt Bf 109 fighter planes. The clash lasted several minutes, as a result of which the Poles dispersed the German formation, causing losses to the enemy. In the Polish literature it was assumed, based on the reports of Polish airmen immediately after the battle and later, that the Polish side managed to shoot down four or five enemy planes. This article, based on Polish and German literature and sources, shows the course of the battle and determines the actual successes and losses sustained in the battle by both the Polish and German sides. In the clash, the Germans definitely lost one plane and three fallen Junkers airmen – pilot Flight Sergeant Willhelm Berchneider, radio operator/gunner Leading Aircraftman Max Zeidler and radio operator/gunner Leading Aircraftman Heinz Sandring. A dozen or so planes returned more or less damaged, and their repair had to take some time for the German ground services. The Polish side, on the other hand, lost four planes, including two badly damaged, which could not be repaired under the prevailing war conditions. Two Poles were also killed. An accidental fatal victim was the mechanic of the 141st Flight the Toruń III/4 Fighter Squadron, Staff Sergeant Franciszek Nawrot, who was killed by a random bullet and a very experienced aviator, Flight Lieutenant Mirosław Leśniewski, who died of his wounds ten days later.